AN ERROR ANALYSIS ON THE USE OF VERBS IN RECOUNT WRITING - Meidulan, Raisha; Susilawati, Endang; Wardah, Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study was carried out to analyze students’ error on the use of verbs in recount text writing made by the second semester English education study program of teacher training and education faculty of Tanjungpura University Pontianak. The method used in this study was descriptive qualitative method. Furthermore, the subject of this study was second semester students of Regular B consisted six students from class A and six students from class B. The data were collected through documentations that researcher took from the lecturer. The result of the error analysis process showed that students committed error into four types: omission, addition, selection, and ordering. From the frequency of each error types, selection took 58.1% of the total errors. Moreover, 25.8% errors fell into addition and 16.1% errors fell into omission; whereas, for ordering, it took 0%. This study revealed that the most dominant errors on the use of verbs in recount text writing done by the students were selection. Keywords: Verbs, Recount, Error